The Effect of Transformational Leadership Style and Organizational Commitment on Employee Performance With Organizational Climate as Intervening Variable - Nugraha, Adi (Golden Ratio of Human Resource Management, 2025)
This study aims to determine the effect of transformational leadership style and organizational commitment on employee performance with the intervening variable of organizational climate at Budi Agung Pati General Hospital. The variables of this study are transformational leadership style, organizational commitment, organizational climate, and employee performance. This research is a study using a quantitative approach. This type of research is associative research or research that examines the influence between variables. The number of research samples taken was 220 respondents from a population of 281 RSU Budi Agung Pati employees. Sampling using probability sampling technique with simple random sampling technique. Data collection using a questionnaire. The results of this study are as follows: transformational leadership style has a positive and significant effect on employee performance, organizational commitment has a positive and significant effect on employee performance, transformational leadership style has a positive and significant effect on organizational climate, organizational commitment has a positive and significant effect on organizational climate and organizational climate has a positive and significant effect on employee performance.